APA Handbook of Giftedness and Talent. 2018
DOI: 10.1037/0000038-043
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and the gifted.

Abstract: Bullying among school-age youth continues to be cause for concern. In a recent U.S. national survey, approximately 28% of 12-to 18-year-old students reported they had been bullied at school during the school year, and victimization was highest among sixth graders (37%) compared to seventh or eighth graders (30% and 31% percent, respectively;Robers, Kemp, & Truman, 2013). It is not surprising that sixth graders reported more bullying, given that this is the year that most students transition to middle school. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…Importantly, similar results for gifted and nonidentified students in both self-perception of cyberbullying and Internet addiction would confirm that being gifted would not be a risk or prevention factor in terms of becoming involved in such situations. This result would reinforce the approach of Mitchell (2011) and Parker and Bain (2011), indicating that being gifted is not a variable that contributes to increased bullying via the Internet; unlike other studies which indicate that being gifted has been related to both a higher (Peterson & Ray, 2006) and lower (Estell et al, 2009) incidence of bullying.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Importantly, similar results for gifted and nonidentified students in both self-perception of cyberbullying and Internet addiction would confirm that being gifted would not be a risk or prevention factor in terms of becoming involved in such situations. This result would reinforce the approach of Mitchell (2011) and Parker and Bain (2011), indicating that being gifted is not a variable that contributes to increased bullying via the Internet; unlike other studies which indicate that being gifted has been related to both a higher (Peterson & Ray, 2006) and lower (Estell et al, 2009) incidence of bullying.…”
Section: Discussionsupporting
confidence: 55%
“…However, in other studies, the opposing conclusion is reached; that is, these students seem to be less vulnerable to bullying and are even less likely to get involved in situations of this type (Estell et al, 2009). Cohen et al (1994) indicated that gifted students, in the last years of primary and first years of secondary, are generally well accepted by their peers, postulating that these students could have low ratios in these situations, with a lower likelihood in the role of victim or aggressor, in comparison with other students.…”
Section: Giftedness and Cyberbullyingmentioning
confidence: 90%
See 2 more Smart Citations
“…La ACI implica una serie de características personales, biológicas, cognitivas y emocionales, que si no se desarrollan en un entorno sociocultural adecuado pueden llevar a la aparición de problemas en el ámbito personal, social y académico (Eren et al, 2018). Los niños y adolescentes con ACI no sólo parecen mostrar una mejor empatía y una mayor preocupación por las injusticias y los problemas del mundo que les rodea, sino que además han sido definidos en numerosas ocasiones como más sensibles e intensos emocionalmente (Espelage y King, 2018;Freeman, 2005;Pfeiffer, 2018). Estas características que podrían actuar como factores de protección ante las adversidades y favorecer un desarrollo socioemocional promedio o superior (Baudson, 2016;Gómez-Péreza et al, 2014;Lee et al, 2012) también podrían suponer una mayor vulnerabilidad a experimentar la soledad física o existencial (Guthrie, 2019;Rinn, 2018;Shechtman y Silektor, 2012).…”
Section: Introductionunclassified